THE RELATIONSHIP BETWEEN PREGNANT WOMEN'S KNOWLEDGE ABOUT PREGNANCY NUTRITION AND THE INCIDENCE OF CHRONIC ENERGY DEFICIENCY (CED) IN PREGNANT WOMEN AT THE TIMBAAN VILLAGE HEALTH POST, BANDAR DISTRICT, SIMALUNGUN REGENCY, NORTH SUMATRA PROVINCE IN 2024 - Hutabarat, Dewi Sartika; Saragih, Fitri Lestari; Putri Bakara, Sri Muliana; Butarbutar, Dyanti SR (Yayasan Nuraini Ibrahim Mandiri, 2025)
Background: The most common nutritional disorder experienced by pregnant women is Chronic Energy Deficiency (CED). CED in pregnant women is a condition of insufficient energy and protein intake during pregnancy that can cause health problems for the mother and fetus. Pregnancy is not a disease, but a normal and natural phenomenon. Pregnant women with Chronic Energy Deficiency (CED) are pregnant women at risk of CED, which is characterized by a mid-upper arm circumference (MUAC) of less than 23.5 cm. Nutritional problems in pregnant women, especially Chronic Energy Deficiency (CED), are a public health problem that affects the health of mothers and fetuses. One factor influencing the incidence of CED is pregnant women's knowledge of nutrition during pregnancy. This study aims to determine the relationship between pregnant women's knowledge of pregnancy nutrition and the incidence of CED at the Timbaan Village Health Post, Bandar District, Simalungun Regency, North Sumatra Province in 2024. Methods: This study was quantitative with a cross-sectional approach. The population was all pregnant women visiting the Timbaan Village Health Post, and a sample of 40 respondents was drawn using a total sampling technique. Data were collected through a questionnaire to determine the level of knowledge of pregnant women and to measure nutritional status using the Mid-Upper Arm Circumference (MUAC). Data were analyzed using univariate and bivariate methods using the chi-square test with a 95% confidence level. Results: The results of the study showed that most pregnant women had insufficient knowledge (57.5%), and most experienced CED (55%). The chi-square test results showed a significant relationship between pregnant women's knowledge of pregnancy nutrition and the incidence of CED (p-value = 0.012 < 0.05). Conclusion: The conclusion of this study is that there is a significant relationship between pregnant women's knowledge of pregnancy nutrition and the incidence of Chronic Energy Deficiency (CED). It is hoped that health workers can improve nutrition education and counseling for pregnant women to prevent CED.